Reverse educational spillovers at the firm level - Backes-Gellner, Uschi [Verfasser]; Rupietta, Christian [Verfasser]; Tuor Sartore, Simone N. [Verfasser] (My University, 2017)
"The purpose of this paper is to examine spillover effects across differently educated workers. For the first time, we consider 'reverse' spillover effects, i.e. spillover effects from secondary-educated workers with dual vocational education and training (VET) to tertiary-educated workers with academic education. We argue that, due to structural differences in training methodology and content, secondary-educated workers with VET degrees have knowledge that tertiary academically educated workers do not have. We use data from a large employer-employee data set: the Swiss earnings structure survey. We estimate OLS and fixed effects panel-data models to identify such 'reverse' spillover effects. Moreover we consider the endogenous workforce composition. We find that tertiary-educated workers have higher productivity when working together with secondary-educated workers with VET degrees. Our instrumental variable estimations support this finding. The functional form of the reverse spillover effect is inverted-U-shaped. This means that at first the reverse spillover effect from an additional secondary-educated worker is positive but diminishing. Our results imply that firms need to combine different types of workers because their different kinds of knowledge produce spillover effects and thereby lead to overall higher productivity." (Authors' abstract, BIBB-Doku)

Dieser Beitrag untersucht auf der Grundlage einer Analyse von Daten der Schweizerischen Lohnstrukturerhebung, wie sich die Qualifikationsstruktur eines Unternehmens auf die Löhne der Mitarbeiter auswirkt. Es kann dabei ein positiver Effekt der Zunahme der Zahl gelernter Facharbeiter auf die Einkommenshöhe der Angestellten mit tertiärer Ausbildung nachgewiesen werden. Dieser Zusammenhang ist zwar degressiv, aber er ist robust und bleibt auch bestehen, wenn verschiedene Kontrollvariablen einbezogen werden, wie Region, Branche oder Erhebungsjahr. Es sind also nicht die akademisch ausgebildeten Angestellten, deren Qualifikationen einseitig den Angestellten mit einer Berufslehre zugute kommen, sondern erstere profitieren ebenfalls von den spezifischen Fachkenntnissen der letzteren. (BIBB-Doku)
Working Paper Version erschienen u.d.T. "Educational Spillovers at the Firm Level: Who Benefits from Whom?" (2015), http://repec.business.uzh.ch/RePEc/iso/leadinghouse/0065_lhwpaper.pdf [Zugriff: 5.3.2018]
Keywords: S 3.2 Unternehmen und Behörden; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; I 2.2.1 Westeuropa; Unternehmen; Qualifikationsstruktur; Einkommensverteilung; Einflussfaktor; Bildungsabschluss; Ausbildungsabschluss; Studienabschluss; Schweiz